Відповідь:1/(√(√(30)+3)-1)-(1/(√(√(30)+3)+1)=(((√(√(30)+3)+1))-((√(√(30)+3)-1))/((√(√(30)+3)+1)(√(√(30)+3)-1)=(1+1)/((√(√(30)+3)²-1²)=2/(√30+3-1)=2/(√30+2)=2*(√30-2)/(30-4)=(√30-2)/13Использовал формулу разности квадратов а²-в²=(а-в)(а+в)
Пояснення:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:1/(√(√(30)+3)-1)-(1/(√(√(30)+3)+1)=(((√(√(30)+3)+1))-((√(√(30)+3)-1))/((√(√(30)+3)+1)(√(√(30)+3)-1)=(1+1)/((√(√(30)+3)²-1²)=2/(√30+3-1)=2/(√30+2)=2*(√30-2)/(30-4)=(√30-2)/13Использовал формулу разности квадратов а²-в²=(а-в)(а+в)
Пояснення: